The Implementation of Project Based Learning Model to Improve Learning Outcomes of Grade XI Social Science Students at SMAN 10 Gowa in Geography Subject - Syamsunardi (Journal of Edugeography, 2025)
Thisi study aims to examine the implementation process of the Project Based Learning (PjBL) model and to analyze the learning outcomes of Grade XI Social Sciences students at SMAN 10 Gowa in the Geography subject, specifically on the topic of Flora and Fauna in Indonesia and the World. Data collection was conducted using observation sheets and tests in each session. The results of this study indicate that the percentage of student activity in the learning process increased from 33.64% in Cycle I to 73.25% in Cycle II. This increase had a positive impact on student learning mastery, with an average score of 78.06 before implementing the Project-Based Learning model. After the implementation, student mastery reached 100% in both Cycle I and Cycle II. The average score in Cycle I was 84.00, while in Cycle II, it increased to 98.83. The percentage increase in students' average Geography learning outcomes from before and after implementing the Project-Based Learning model was 7.61% in Cycle I and 10.05% in Cycle II.